2020
DOI: 10.1101/2020.03.26.008714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioral, physiological, and neural signatures of surprise during naturalistic sports viewing

Abstract: length: 150 words Abstract Surprise signals a discrepancy between predicted and observed outcomes. It is theorized to segment the flow of experience into discrete perceived events, drive affective experiences, and create particularly resilient memories. However, the ability to precisely measure naturalistic surprise has remained elusive. We used advanced basketball analytics to derive a quantitative measure of surprise and characterized its behavioral, physiological, and neural effects on human subjects observ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 97 publications
(94 reference statements)
2
8
0
Order By: Relevance
“…In that experiment, participants were periodically asked to rate their boredom, and the authors found that this measure was inversely correlated with changes in prediction errors, a proxy for the amount of information being acquired in the task the dynamics of which, in turn, differed between conditions according to what could be learned. A similar relationship between prediction error and boredom has been measured in Antony et al (2020).…”
Section: Empirical Findingssupporting
confidence: 74%
“…In that experiment, participants were periodically asked to rate their boredom, and the authors found that this measure was inversely correlated with changes in prediction errors, a proxy for the amount of information being acquired in the task the dynamics of which, in turn, differed between conditions according to what could be learned. A similar relationship between prediction error and boredom has been measured in Antony et al (2020).…”
Section: Empirical Findingssupporting
confidence: 74%
“…In sum, our choice of the spatial aperture of large functional networks is well tuned to highlight the transition from resting-state dynamics to those evoked by movie immersion. Alternative approaches reveal other complex features of these rich neuronal dynamics, including the role of state transitions in scene completion 58,59 , narrative segmentation 60 , and memory encoding 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Future investigations should determine whether the correspondence of hippocampal activity at event boundaries with memory for preceding and subsequent events reflects one common, underlying process (e.g. updating representations in response to high prediction error; Antony et al, 2020;Bein et al, 2020;Franklin et al, 2020;Lu et al, 2020;Sinclair et al, 2020) or two overlapping processes (e.g. memory storage vs retrieval).…”
Section: Discussionmentioning
confidence: 99%